Pengaruh Media Video Audiovisual terhadap Pengetahuan Kepatuhan Diet Pasien Gagal Ginjal yang Menjalani Hemodialisis - Apriyani, Apriyani; Agustina, Silvia; Susanti, Sherly (Jurnal Akademika Baiturrahim Jambi, 2026)
Background: CKD is a chronic non-infectious disorder, quite common and affects approximately one in ten adults worldwide. The number of CKD patients undergoing hemodialysis (HD) is estimated at around 1.5 million people worldwide, with the incidence projected to increase by 8% annually. Uncontrolled food and fluid intake has the potential to cause malnutrition, even in more severe conditions it can lead to death. Education plays an important role in increasing patient knowledge regarding dietary compliance, one effort to increase respondent knowledge is using audiovisual video media. Research Objective: This study aims to determine the Effect of Animated Videos on Knowledge of Diet Compliance in Kidney Failure Patients Undergoing Hemodialysis at Muhammadiyah Hospital Palembang. Research Method: This study is a quantitative study with a one-group pretest-posttest design. The sampling technique is purposive sampling with a total of 30 respondents at Muhammadiyah Hospital Palembang with inclusion criteria of those suffering from chronic kidney failure who are undergoing hemodialysis regularly twice a week. Results: The median knowledge value before the intervention was 9.00 and after the intervention was 14.00. Statistical tests using the Wilcoxon Test showed a significant P value of 0.001 (<0.05). Conclusion: shows a statistically significant increase in knowledge. Research suggestion: with the results of this study, it is recommended to make video media a routine educational program for chronic kidney failure patients undergoing hemodialysis, because it has been proven to increase knowledge of dietary compliance